2005
DOI: 10.1159/000086073
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation in Italian Families with Stargardt Disease

Abstract: Autosomal recessive Stargardt disease (STGD) has been associated with substantial genetic and phenotypic heterogeneity. By systematic clinical analyses of STGD patients with complete genetic data (i.e. identified mutations on both alleles of the ABCA4 gene), we set out to determine phenotypic subtypes and to correlate these with specific ABCA4 alleles. Twenty-eight patients from 18 families with STGD/fundus flavimaculatus were investigated. All patients were submitted to complete ophthalmologic examination, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 50 publications
0
45
1
Order By: Relevance
“…Therefore, it can be speculated that its clinical expression depends on the mutation severity on the fellow allele, as suggested by earlier genotype/ phenotype studies. 17,21 Still, although the A1038V mutation is commonly reported in the literature, 9,13,27 in our series, it was detected in only two patients (1.4% of the patients, 0.7% of the alleles) within the L541P-A1038V complex allele. Moreover, in the Italian studies, this mutation was reported in 4.1 10 and 5.5% 11 of the alleles.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Therefore, it can be speculated that its clinical expression depends on the mutation severity on the fellow allele, as suggested by earlier genotype/ phenotype studies. 17,21 Still, although the A1038V mutation is commonly reported in the literature, 9,13,27 in our series, it was detected in only two patients (1.4% of the patients, 0.7% of the alleles) within the L541P-A1038V complex allele. Moreover, in the Italian studies, this mutation was reported in 4.1 10 and 5.5% 11 of the alleles.…”
Section: Discussioncontrasting
confidence: 42%
“…11 In addition, another study on an Italian sample considered only patients with biallelic disease mutations for a genotype-phenotype correlation. 17 In this study, the mutation spectrum of the ABCR gene was determined in another group of Italian patients affected with autosomal recessive STGD. Our series consisted of 62 families, originating for the most part from the central Italy.…”
Section: Introductionmentioning
confidence: 99%
“…22 The heterozygous G1961E mutation, in combination with a different ABCA4 allele on the other chromosome, has been associated with a localized disease process that is confined to the posterior pole, normal full-field electroretinogram (ffERG), absence of the ''dark choroid'' sign on fluorescein angiography (FA), and BEM on fundus autofluorescence (FAF). 19,[23][24][25] Despite all these data, there still is debate as to whether this mutation causes retinal pathology in homozygosity. We studied patients homozygous for the G1961E allele to demonstrate the pathogenicity of the mutation in homozygosity and to describe further the variation in retinal phenotypes associated with it.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype for the heterozygous cases is similar to that reported by Simonelli and colleagues. 3 Collectively, these reports suggest that there may not be a meaningful difference in the phenotype and specifically the age of onset between homozygous and heterozygous carriers of the G1961E mutation. …”
mentioning
confidence: 99%